Features of recreation land use and settlement of suburban areas of large cities - Oliinyk, Valentyna (Human Geography Journal, 2022)
The article highlights theoretical and practical issues of agricultural land use in Ukraine and examines foreign experience. An in-depth scientific analysis of international and domestic literature has been carried out. On this basis the main patterns and trends of land use development, the main factors and consequences of suburbanization, the basics of developing the Concept of state regional policy, the world experience of land lease and the stages of land relations reform in Ukraine have been identified. The main factors influencing suburbanization and the use of suburban territories are considered. The necessity of delimiting suburban areas and developing a project of inter-farm land use, which should take into account the peculiarities of geographical location and socio-economic consequences, environmental factor, is noted. The analysis of statistical data on the use of land areas of Ukraine is carried out. Tasks have been identified, the implementation of which will contribute to the development of socio-economic conditions of settlements in the suburban area. It is indicated the need to conduct land use taking into account environmental requirements, compliance with the rules of environmental protection, land resources. The use of land resources of different countries is investigated. The analysis of the efficiency of land use and methods of farming in developed countries is carried out. Aspects of agricultural production support are considered: The regulatory mechanism in different countries is characterized by a variety of financial and economic instruments that change in accordance with the political and economic situation. The state policy of Ukraine regarding land use and the main provisions of agribusiness support are investigated. The necessity of developing methodological provisions for the implementation of land ownership rights is noted. It is pointed out the importance of ensuring the equivalence of exchange at all stages of the movement of the created value from the field to the final consumer.